Services sectors' agglomeration and its interdependence with industrial agglomeration in the European Union - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
Services sectors' agglomeration in the European Union, its development over time, its driving factors and dynamic tendencies will be empirically investigated in this study. Locational gini coefficients are computed taking EU-KLEMS data for 14 European countries covering 22 services sectors over the period from 1970 to 2005. Services sectors' agglomeration in the European Union decreased over the years between 1970 and 2005. Analysis shows that for most of the services sectors considered agglomeration decreased over time, leading to further dispersion of economic activities. Only the branches of retail trade, other water transport and financial intermediation record a significant increase in agglomeration. Agglomeration tendencies of services sectors can be best explained by Traditional and New Trade Theories, New Economic Geography appears to be not relevant. Theoretical work, incorporating services sectors' activities in New Economic Geography models, is scarce and as Empirics show there is a justified reason for lack of research in that area. In a further step the interaction between industrial and services sectors' agglomeration is investigated. Non-stationarity of variables is being checked for and error correction methods or regression in differences is employed. There exist several interactions between services and industrial sectors' agglomeration in the European Union. In particular, agglomeration in retail trade is positively ifluenced by an increase in agglomeration in textiles industries over the years between 1970 and 2005. The existence of interaction effects justifies further enhancement of theoretical models. Further, the results are important for understanding agglomeration processes in the EU; interactions between services and industrial sectors are indicative for a highly dynamic region which might attract other activities, as well.
Keywords: C50; F12; F14; F15; L80; 330; Services; Agglomeration; New Economic Geography; European Integration; Dienstleistungssektor; Regionales Cluster; Produktionsstandort; Neue Ökonomische Geographie; Wirtschaftsintegration; Schätzung; EU-Staaten